A manganese-based sodium ion battery positive electrode material and preparation method thereof, positive electrode sheet and sodium ion secondary battery
By using an O3-type layered oxide structure with R-3M space group and metal elements without redox function in the sodium ion battery positive electrode material, combined with Fe and Mn, a high-capacity and low-cost manganese-based sodium ion battery is formed. The positive electrode material solves the problems of high cost and low capacity of the existing sodium ion battery cathode materials, and achieves reversible capacity of more than 180mAh/g and stable cycling performance.
Patent Information
- Application Number
- CN202411104749.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The high nickel content of existing sodium ion battery cathode materials leads to high costs and low capacity cannot meet the actual application needs.
The positive electrode material of manganese-based sodium ion battery with an O3-type layered oxide structure with an R-3M space group is NaxM1aFebMncO2, combined with metal elements that do not have redox functions such as Li, Mg, Zn, Ca, Al and Fe, Mn, a high capacity, low cost positive electrode material is formed through specific calcination and cooling processes.
By regulating the material composition and structure, the reversible capacity of the positive electrode material is improved, the reversible discharge specific capacity of more than 180mAh/g is achieved, and the cost is reduced and the circulation performance is improved.
Smart Images

Figure CN118645615B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a manganese-based sodium ion battery positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion secondary battery. Background Art
[0002] Over the past few decades, lithium-ion batteries have been widely used in portable electronic devices, hybrid electric vehicles, and electric vehicles. However, the limitation of lithium resources has raised concerns about lithium-ion batteries as a sustainable and ideal energy storage battery option. Due to the wide availability and low cost of sodium resources, as well as the low temperature performance and rate characteristics of sodium-ion batteries, the industry has gradually realized the importance of sodium-ion batteries in the field of new energy storage batteries. Finding cathode materials with high energy density and low cost will definitely be a key factor in promoting the industrialization of sodium-ion batteries. Various sodium-containing compounds have been intensively studied as cathode materials for sodium-ion batteries. Among them, layered transition metal sodium oxides Na x MO 2 (M can be Mn, Co, Cr, Fe, V) is considered to be one of the most promising positive electrode materials for industrialization due to its different structures and controllability of components.
[0003] Among the Na transition metal oxides with different structures and compositions, Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O 2 , NaLi 0.2 Ni 0.25 Mn 0.75 O 2 、Na x Fe y Mn 1-y O 2 and NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Materials such as NaNi and Mg have been proven to be electrochemically active. Although a certain energy density can be achieved by designing and regulating the components and structures, combined with the selection and combination of different transition metal elements, the O3-type layered oxide cathode material NaNi that is currently close to industrialization 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2The reversible capacity is basically 130-150mAh / g. The capacity of these sodium-ion battery cathode materials is much lower than that of high-nickel ternary cathode materials for lithium-ion batteries, and even lower than that of low-cost lithium iron phosphate cathode materials. At the same time, the high content of nickel metal elements (>20%) in this type of material increases the cost of cathode materials. Therefore, research and development of high-capacity, low-cost cathode materials is of great significance to accelerate the industrialization and application of sodium-ion batteries.
[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0005] In view of the deficiencies in the prior art, a manganese-based sodium ion battery positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion secondary battery are provided to solve the problem that the current sodium ion battery positive electrode material has a high nickel content resulting in high cost and a low capacity that cannot meet practical applications. The manganese-based positive electrode material of the present invention has the advantages of high capacity and low cost.
[0006] In order to achieve the above object, on the one hand, the present invention provides a manganese-based sodium ion battery positive electrode material, which is as follows:
[0007] A manganese-based sodium ion battery positive electrode material, the positive electrode material is an O3-type layered oxide with an R-3M space group, and the chemical formula of the positive electrode material is Na x M1 a Fe b Mn c O 2 , 0.6≤x≤1.0, 0.05≤a≤0.4, 0.1≤b≤0.45, 0.4≤c≤0.6, a+b+c=1, M1 is a metal element that does not have redox function in the solid phase, and M1 is selected from at least one of Li, Mg, Zn, Ca, and Al; in the XRD spectrum of the positive electrode material, the peak intensity ratio of the crystal plane diffraction peak (003) to (104) is 0.5≤I (003) / I (104) ≤0.98; in the Raman scattering spectrum of the positive electrode material, at 660-680cm -1 The characteristic peak S appears in the range of 565-580cm -1 Characteristic peak B appears in the range, and the peak intensity ratio of the two is 0.3≤I S / I B ≤0.8.
[0008] Preferably, the positive electrode material Na x M1 a Fe b Mn c O 2, 0.7≤x≤0.9, 0.1≤a≤0.35, 0.1≤b≤0.3.
[0009] Preferably, the positive electrode material Na x M1 a Fe b Mn c O 2 The crystal plane peak intensity ratio is 0.6≤I (003) / I (104) ≤0.9.
[0010] Preferably, 0.4≤I S / I B ≤0.7.
[0011] On the other hand, the present invention also provides a method for preparing a manganese-based sodium ion battery positive electrode material, which is as follows:
[0012] A method for preparing a manganese-based sodium ion battery positive electrode material comprises the following steps:
[0013] S1: A certain proportion of Na salt, M1 source, Fe source and Mn source are fully mixed by ball milling method, and dried to obtain a reaction mixture precursor, wherein the M1 source, Fe source and Mn source are selected from oxides, acetates or nitrates of corresponding metals;
[0014] S2: calcining the reaction mixture precursor of step S1 at 700° C.-800° C. for 2-6 hours to obtain a calcined precursor 1;
[0015] S3: calcining the calcined precursor 1 in step S2 at 800° C.-1050° C. for 10-20 h to obtain a calcined precursor 2;
[0016] S4: rapidly cooling the calcined precursor 2 to 400-600° C. and maintaining the temperature for 3-6 hours to obtain a positive electrode material precursor;
[0017] S5: Naturally cool the positive electrode material precursor to room temperature to obtain a manganese-based sodium ion battery positive electrode material.
[0018] Preferably, the calcination temperature in step S2 is 750°C-800°C, and the heating rate is 2-10°C / min.
[0019] Preferably, the calcination temperature in step S3 is 900° C.-1000° C., and the heating rate is 2-5° C. / min.
[0020] Preferably, in step S4, the calcined precursor 2 is rapidly cooled to 430-560° C. and maintained for 4-5 hours.
[0021] In addition, the present invention also provides a positive electrode sheet, which includes the above-mentioned manganese-based sodium ion battery positive electrode material.
[0022] Finally, the present invention also provides a sodium ion secondary battery, which includes a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet is the positive electrode sheet described above including the above-mentioned manganese-based sodium ion battery positive electrode material.
[0023] The beneficial effects of the present invention are as follows: the positive electrode material provided by the present invention is dominated by manganese and has low cost. It also combines the M1 element without redox function and the transition metal element Fe with redox function. By regulating the material components and structure, the positive electrode material can induce the redox reaction of anions on the basis of the redox reaction of the transition metal it carries, and the redox reaction of the anions has high reversibility, thereby greatly increasing the number of sodium ions that can be reversibly deintercalated and intercalated in the structure, thereby improving the reversible capacity of the positive electrode material. The reversible discharge specific capacity of the positive electrode active material of the present invention reaches more than 180 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 (a) and (b) are the XRD spectrum and Raman spectrum of the positive electrode material of Example 3 of the present invention, respectively.
[0025] Figure 2 (a) and (b) are the XRD spectrum and Raman spectrum of the positive electrode material of Example 12 of the present invention, respectively.
[0026] Figure 3 (a) and (b) are respectively the XRD spectrum and Raman spectrum of the positive electrode material of Comparative Example 1 of the present invention.
[0027] Figure 4 (a) and (b) are respectively the XRD spectrum and Raman spectrum of the positive electrode material of Comparative Example 3 of the present invention.
[0028] Figure 5 This is the charge and discharge curve of the positive electrode material of Example 12 of the present invention.
[0029] Figure 6 The Na x M1 a Fe b Mn c O 2 Schematic diagram of the energy band of positive electrode materials. DETAILED DESCRIPTION
[0030] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0031] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0032] In view of the shortcomings of the prior art, a manganese-based sodium ion battery positive electrode material is provided to solve the problem that the current sodium ion battery positive electrode material has a high nickel content, resulting in high cost, and the capacity is still low and cannot meet the practical application. The manganese-based positive electrode material of the present invention has the advantages of high capacity and low cost.
[0033] In order to achieve the above object, on the one hand, the present invention provides a manganese-based sodium ion battery positive electrode material, which is as follows:
[0034] A manganese-based sodium ion battery positive electrode material, the positive electrode material is an O3-type layered oxide with an R-3M space group, and the chemical formula of the positive electrode material is Na x M1 a Fe b Mn c O 2 , 0.6≤x≤1.0, 0.05≤a≤0.4, 0.1≤b≤0.45, 0.4≤c≤0.6, a+b+c=1, M1 is a metal element that does not have redox function in the solid phase, and M1 is selected from at least one of Li, Mg, Zn, Ca, and Al; in the XRD spectrum of the positive electrode material, the peak intensity ratio of the crystal plane diffraction peak (003) to (104) is 0.5≤I (003) / I (104) ≤0.98; in the Raman scattering spectrum of the positive electrode material, at 660-680cm -1 The characteristic peak S appears in the range of 565-580cm -1 Characteristic peak B appears in the range, and the peak intensity ratio of the two is 0.3≤I S / I B ≤0.8.
[0035] Among them, the content x of Na can be 0.6≤x<0.7, 0.7≤x<0.8, 0.8≤x<0.82, 0.82≤x<0.85, 0.85≤x<0.9 or 0.9≤x≤1.0. Preferably, the value of x can be 0.7≤x≤0.9. The Na content within this range is used in combination with M1, Fe, and Mn elements to induce a reversible redox reaction of anions, while ensuring the conductivity and cycle stability of the positive electrode active material.
[0036] Regarding the M1 element, a part of the metal element that does not have redox activity in the solid phase is added to the positive electrode material, and it is combined with Fe and Mn elements to obtain a positive electrode material with a local ordered structure. On the contrary, compared with the conventional combination of metal elements containing only redox activity, the positive electrode active material as a whole also has the function of inducing the oxidation-reduction reaction of anions, increasing the number of reverse deintercalation-embedded sodium ions, thereby improving the reversible capacity of the positive electrode material, and the subsequent cycle performance is also improved after the structure is more stable. Preferably, the M1 element is Mg and Zn. The present invention breaks the conventional practice of blindly using only positive electrode active materials composed of redox-active metal elements. By regulating the element composition, even if the redox-active metal elements in the system are relatively reduced, the redox reaction of anions is brought about, so that the number of reverse deintercalation-embedded sodium ions is relatively more, thereby achieving an improvement in reversible capacity and cycle performance.
[0037] Regarding Fe and Mn in the positive electrode material, the use of a certain proportion of metal elements M1, Fe, and Mn can obtain a more stable local ordered structure with higher reversible capacity and cycle performance.
[0038] Regarding the microstructure of the positive electrode material, when the peak intensity ratio of the crystal plane diffraction peak (003) to (104) in the XRD spectrum is 0.5≤I (003) / I (104) ≤0.98, Raman scattering spectrum, 660-680cm -1 The characteristic peak S appears in the range of 565-580cm -1 Characteristic peak B appears in the range, and the peak intensity ratio of the two is 0.3≤I S / I B ≤0.8, at this time, the positive electrode material has a better layered structure, which is conducive to enhancing the interaction between transition metal elements and oxygen, thereby improving the capacity and stability of the positive electrode material.
[0039] Preferably, the positive electrode material Na x M1 a Fe b Mn c O 2, 0.1≤a≤0.35, 0.1≤b≤0.3.
[0040] Preferably, the positive electrode material Na x M1 a Fe b Mn c O 2 The crystal plane peak intensity ratio is 0.6≤I (003) / I (104) ≤0.9.
[0041] Preferably, 0.4≤I S / I B ≤0.7.
[0042] On the other hand, the present invention also provides a method for preparing a manganese-based sodium ion battery positive electrode material, which is as follows:
[0043] A method for preparing a manganese-based sodium ion battery positive electrode material comprises the following steps:
[0044] S1: A certain proportion of Na salt, M1 source, Fe source and Mn source are fully mixed by ball milling method, and dried to obtain a reaction mixture precursor, wherein the M1 source, Fe source and Mn source are selected from oxides, acetates or nitrates of corresponding metals;
[0045] S2: calcining the reaction mixture precursor of step S1 at 700° C.-800° C. for 2-6 hours to obtain a calcined precursor I;
[0046] S3: calcining the calcined precursor 1 in step S2 at 800° C.-1050° C. for 10-20 h to obtain a calcined precursor II;
[0047] S4: rapidly cooling the calcined precursor 2 to 400-600° C. and maintaining the temperature for 3-6 hours to obtain a positive electrode material precursor;
[0048] S5: Naturally cool the positive electrode material precursor to room temperature to obtain a manganese-based sodium ion battery positive electrode material.
[0049] In the step-by-step calcination-step-by-step cooling method of the present invention, the heating process of the reaction is more conducive to the formation of a highly ordered internal structure of the positive electrode material, and the rapid cooling after the calcination is more conducive to the further improvement of the crystal form, which can significantly reduce the defects of the internal structure, thereby improving the reversible capacity and cycle performance of the material.
[0050] Preferably, the calcination temperature in step S2 is 750°C-800°C, and the heating rate is 2-10°C / min.
[0051] Preferably, the calcination temperature in step S3 is 900° C.-1000° C., and the heating rate is 2-5° C. / min.
[0052] Preferably, in step S4, the calcined precursor 2 is rapidly cooled to 430-560° C. and maintained for 4-5 hours.
[0053] In addition, the present invention also provides a positive electrode sheet, which includes the above-mentioned manganese-based sodium ion battery positive electrode material. Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, and the positive electrode active material in the positive electrode active material layer is the positive electrode material of the present invention. The positive electrode active material layer also includes currently commonly used binders, conductive agents, etc. The binder includes but is not limited to at least one of SBR, PAA, PI, PAN, and PVDF, and the conductive agent includes but is not limited to carbon black (such as Super-P, KS-6), VGCF, multi-walled CNT, and single-walled CNT. At least one or more of them will not be repeated here.
[0054] The positive electrode current collector can be any material suitable for use as a positive electrode current collector for a sodium ion battery in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to aluminum foil.
[0055] Specifically, the preparation method of the positive electrode sheet can be prepared according to the conventional preparation method of the positive electrode sheet, such as the following method: the positive electrode material, the conductive agent, and the binder of the present invention are prepared into a slurry according to a proportion, and then coated, rolled, and die-cut at a certain surface density to obtain a positive electrode sheet. In the slurry, the positive electrode material of the present invention can account for 85wt%-97wt%, the conductive agent can account for 0.01wt%-5wt%; and the binder can account for 0.1wt%-8wt%.
[0056] In addition, the present invention also provides a sodium ion secondary battery, which includes a positive electrode sheet, a negative electrode sheet, and a separator spaced between the positive electrode sheet and the negative electrode sheet.
[0057] The positive electrode sheet is the positive electrode sheet including the above-mentioned manganese-based sodium ion secondary battery positive electrode material. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may be one or more of soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, tin-based materials, oxide-type negative electrode materials or other metals that can form alloys with sodium. Among them, the carbon-based negative electrode material can be selected from one or more of soft carbon, hard carbon, carbon fiber, and mesophase carbon microspheres; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials suitable for use as a negative electrode current collector for sodium ion batteries in the art. For example, the negative electrode current collector can be, but is not limited to, metal foil, etc., and more specifically, it can be, but is not limited to, aluminum foil and copper foil. In order to facilitate the detection of the performance of the positive electrode material, a sodium sheet can also be directly used as a negative electrode to assemble a sodium ion secondary battery.
[0058] The separator can be any material suitable for sodium ion secondary battery separators in the art, for example, it can be a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber, etc. It can also be a solid electrolyte membrane with ion conduction function.
[0059] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0060] Example 1
[0061] A manganese-based sodium ion battery positive electrode material, the positive electrode material is an O3-type layered oxide with an R-3M space group, and the chemical formula of the positive electrode material is Na 0.8 Mg 0.05 Fe 0.45 Mn 0.5 O 2 , and its preparation method is specifically as follows:
[0062] S1: Mix Na and 2 CO 3 MgCO 3 , Fe 2 O 3 , Mn 2 O 3 , wet ball milled at 400 rpm for 12 h, and then dried at 120 °C for 6 h to obtain a reaction mixture precursor;
[0063] S2: calcining the reaction mixture precursor of step S1 at 750° C. for 3 h to obtain a calcined precursor 1;
[0064] S3: calcining the calcined precursor 1 in step S2 at 950° C. for 15 h to obtain a calcined precursor 2;
[0065] S4: rapidly cooling the calcined precursor 2 to 450° C. and maintaining the temperature for 4 h to obtain a cathode material precursor;
[0066] S5: Cool the cathode material precursor naturally to room temperature to obtain the manganese-based sodium ion battery cathode material Na 0.8 Mg 0.05 Fe 0.45 Mn 0.5 O 2 .
[0067] Embodiment 2-4
[0068] Different from Example 1, the positive electrode material of this embodiment is Na 0.8 Mg 0.1 Fe 0.4 Mn 0.5 O 2 , Na 0.8 Mg 0.2 Fe 0.3 Mn 0.5 O 2 , Na 0.8 Mg 0.3 Fe 0.2 Mn 0.5 O 2 , the preparation can be carried out by adjusting the added content according to the different molar ratios of each element, as shown in Example 1, which will not be repeated here.
[0069] Embodiment 5-8
[0070] Different from Examples 1-4, M1 in Examples 5-8 is Zn, and the positive electrode material obtained is Na 0.8 Zn 0.05 Fe 0.45 Mn 0.5 O 2 , Na 0.8 Zn 0.1 Fe 0.4 Mn 0.5 O 2 , Na 0.8 Zn 0.2 Fe 0.3 Mn 0.5 O 2 , Na 0.8 Zn 0.3 Fe 0.2 Mn0.5 O 2 , the preparation can be carried out by adjusting the added content according to the different molar ratios of each element, as shown in Example 1, which will not be repeated here.
[0071] Examples 9-11
[0072] Different from Example 1, M1 in Examples 9-11 is a combination of two elements, and the obtained positive electrode material is Na 0.8 (Li 0.1 Al 0.05 )Fe 0.35 Mn 0.5 O 2 、Na 0.8 (Zn 0.1 Ca 0.1 )Fe 0.3 Mn 0.5 O 2 , Na 0.8 (Li 0.05 Mg 0.15 )Fe 0.3 Mn 0.5 O 2 , the preparation can be carried out by adjusting the added content according to the different molar ratios of each element, as shown in Example 1, which will not be repeated here.
[0073] Examples 12-13
[0074] Different from Example 1, M1 in Examples 12-13 is a combination of three elements, and the obtained positive electrode material is Na 0.8 (Li 0.05 Mg 0.1 Al 0.05 )Fe 0.3 Mn 0.5 O 2 、Na 0.8 (Li 0.06 Ca 0.05 Zn 0.09 )Fe 0.3 Mn 0.5 O 2 , the preparation can be carried out by adjusting the added content according to the different molar ratios of each element, as shown in Example 1, which will not be repeated here.
[0075] Comparative Example 1
[0076] Different from Example 1, the positive electrode active material of this comparative example is Na 0.8 Fe 0.5 Mn 0.5 O 2, the preparation can be carried out by adjusting the added content according to the different molar ratios of each element, as shown in Example 1, which will not be repeated here.
[0077] Comparative Example 2
[0078] Different from Example 1, the positive electrode active material of this comparative example is Na 0.8 Fe 0.3 Mn 0.7 O 2 , the preparation can be carried out by adjusting the added content according to the different molar ratios of each element, as shown in Example 1, which will not be repeated here.
[0079] Comparative Example 3
[0080] The positive electrode active material of this comparative example is Na 0.8 Mg 0.2 Fe 0.3 Mn 0.5 O 2 Unlike Example 3, this comparative example does not adopt the step-by-step calcination-distributed cooling method, but directly calcines the reaction mixture precursor at 950° C. for 18 h and then naturally cools to room temperature. The remaining steps are the same as those in Example 1.
[0081] XRD and Raman tests were performed on the positive electrode materials obtained in Examples 1-13 and Comparative Examples 1-3, respectively. In the XRD spectrum, the peak intensity ratio of the crystal plane diffraction peak (003) to (104) is I (003) / I (104) , Raman scattering spectrum, at 660-680cm -1 The characteristic peak S appears in the range of 565-580cm -1 The characteristic peak B appears in the range, and the peak intensity ratio of the two is I S / I B , the data are shown in Table 1.
[0082] The XRD pattern and Raman pattern of Example 3 are as follows Figure 1 shown.
[0083] The XRD pattern and Raman pattern of Example 12 are as follows: Figure 2 shown.
[0084] The XRD pattern and Raman pattern of Comparative Example 1 are as follows Figure 3 shown.
[0085] The XRD pattern and Raman pattern of Comparative Example 3 are as follows: Figure 4 shown.
[0086] The positive electrode material is then applied to the positive electrode sheet. The preparation method of the positive electrode sheet is as follows: the positive electrode material, polyvinylidene fluoride and SP-P are mixed and ball-milled in a mass ratio of 90:5:5 to obtain a positive electrode slurry, the positive electrode slurry is coated on the surface of the aluminum foil, rolled, vacuum dried at 160°C overnight, and then cold pressed and die-cut to obtain the positive electrode sheet.
[0087] The obtained positive electrode sheet was applied to R2032 button battery for electrochemical performance test. The positive electrode sheet was used as the working electrode, sodium foil was used as the counter electrode, the separator was GB-100R separator, and the non-aqueous electrolyte was used as the electrolyte (the specific preparation method was: ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and NaPF was added 6 , forming the electrolyte, NaPF 6 The concentration is 1 mol / L), and a sodium ion button battery is prepared. Please refer to the existing preparation method, which will not be described here.
[0088] The obtained sodium ion button battery was subjected to constant temperature current charge and discharge test in a constant temperature box at about 25°C, with a test voltage range of 1.5-4.3V and a current density of C / 20 (about 12.0mAg -1 ).
[0089] The performance test results are shown in Table 1 and Figure 5 shown.
[0090] Table 1
[0091]
[0092] Figure 1 The positive electrode material Na prepared according to the composition and synthesis method in Example 3 0.8 Mg 0.2 Fe 0.3 Mn 0.5 O 2 XRD spectrum and Raman spectrum. It can be seen that the obtained positive electrode material belongs to the structure of O3 type material, and The nearby (003) peak and The intensity ratio of the nearby (104) peak is about 0.76. In the Raman spectrum, I S / I B It is about 0.62, which indicates that the synthesized material has few structural defects and a good layered structure.
[0093] Figure 2 The positive electrode material Na prepared according to the composition and synthesis method in Example 12 0.8 (Li 0.05 Mg 0.1 Al 0.05 )Fe 0.3 Mn 0.5O 2 XRD spectrum and Raman spectrum. It can be seen that the obtained positive electrode material belongs to the structure of O3 type material, and The nearby (003) peak and The intensity ratio of the nearby (104) peak is about 0.69. In the Raman spectrum, I S / I B It is about 0.63, which indicates that the synthesized material has few structural defects and a good layered structure.
[0094] Figure 3 The XRD spectrum and Raman spectrum of the positive electrode material prepared according to the components and synthesis method in Comparative Example 1. Similar to Example 3, the material belongs to O3 type layered oxide. The obvious difference is The nearby (003) peak and The intensity ratios of the (104) peaks near the S / I B It is significantly less than 0.3, indicating that there are obvious structural defects in the layers of the synthesized material. It can be seen that by adding a part of the metal element M1 that does not have redox activity in the solid phase to the positive electrode material and combining it with Fe and Mn elements, a positive electrode material with a local ordered structure is obtained. On the contrary, compared with the conventional combination of metal elements that only contain redox activity, the positive electrode active material as a whole also has the function of inducing the oxidation-reduction reaction of anions, increasing the number of reverse deintercalation-intercalation sodium ions, thereby improving the reversible capacity of the positive electrode material, and the subsequent cycle performance is also improved after the structure is more stable.
[0095] Figure 4 The XRD spectrum and Raman spectrum of the positive electrode material prepared according to the components and synthesis method in Comparative Example 3. Similar to Example 3, the material belongs to O3 type layered oxide. The obvious difference is The nearby (003) peak and The intensity of the (104) peak near is about 0.95, close to the boundary value of 0.98, and I S / I B The value of is about 0.38, which is close to the boundary value of 0.3, indicating that there are certain structural defects in the layers of the synthesized material. It can be seen that the preparation method of directly heating the mixture precursor to about 1000℃ for calcination and naturally cooling it to room temperature after calcination will cause certain structural defects, which is not conducive to the formation of an orderly internal structure of the material. Step-by-step calcination can significantly reduce the defects of the internal structure, thereby improving the reversible capacity and cycle performance of the material.
[0096] Figure 5The charge and discharge curve results of the positive electrode material of Example 12 are shown. The first charge capacity is close to 200 mAh / g, and the first discharge capacity can reach 218 mAh / g. Such a high reversible capacity has exceeded the capacity that can be contributed by the redox reaction of Fe and Mn in this component. At the same time, combined with the appearance of a charging platform around 4.0V in the charge and discharge curve, it can be inferred that the redox of oxygen ions also participates in the charge compensation during the charge and discharge process.
[0097] Figure 6 The cathode material Na x M1 a Fe b Mn c O 2 The energy band diagram of can well explain the mechanism of high capacity charge compensation of each component material in the present invention. Figure 6 Where (a) is a=0, which means that the inactive metal elements contained in M1 are not included. Figure 6 (b) in the formula is a>0, i.e., it contains at least one inactive metal element included in M1. The presence of M1 ions on the transition metal layer sites of Na-containing layered oxides can activate oxygen redox reactions because it forms oxygen lone pairs associated with non-bonding O-2p states in the electronic structure. Compared with the Na-O-Mn interaction, the more ionic Na-O-M1 interaction places the O-2p state at a higher energy position (close to the Fermi level), making it easier for oxygen ions to undergo oxygen redox reactions. In addition, these elevated non-bonding O-2p orbitals are very active and can provide or receive additional charges during the intercalation or deintercalation of sodium ions. Therefore, the introduction of this local structure facilitates the oxygen redox process and enhances the specific capacity of the material.
[0098] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A manganese-based sodium ion battery positive electrode material, characterized in that: The positive electrode material is an O3-type layered oxide having an R-3M space group, and the chemical formula of the positive electrode material is Na x M1 a Fe b Mn c O2, 0.6≤x≤1.0, 0.05≤a≤0.4, 0.1≤b≤0.45, 0.4≤c≤0.6, a+b+c=1, M1 is a metal element that does not have redox function in the solid phase, and M1 is selected from at least one of Li, Mg, Zn, Ca, and Al; in the XRD spectrum of the positive electrode material, the peak intensity ratio of the crystal plane diffraction peak (003) to (104) is 0.5≤I (003) / I (104) ≤0.98; in the Raman scattering spectrum of the positive electrode material, at 660-680cm -1 The characteristic peak S appears in the range of 565-580cm -1 Characteristic peak B appears in the range, and the peak intensity ratio of the two is 0.3≤I S / I B ≤0.8; The method for preparing the manganese-based sodium ion battery positive electrode material comprises the following steps: S1: A certain proportion of Na salt, M1 source, Fe source and Mn source are fully mixed by ball milling method, and dried to obtain a reaction mixture precursor, wherein the M1 source, Fe source and Mn source are selected from oxides, acetates or nitrates of corresponding metals; S2: calcining the reaction mixture precursor of step S1 at 700° C.-800° C. for 2-6 hours to obtain a calcined precursor 1; S3: calcining the calcined precursor 1 in step S2 at 800° C.-1050° C. for 10-20 h to obtain a calcined precursor 2; S4: rapidly cooling the calcined precursor 2 to 400-600° C. and maintaining the temperature for 3-6 hours to obtain a positive electrode material precursor; S5: Naturally cool the positive electrode material precursor to room temperature to obtain a manganese-based sodium ion battery positive electrode material.
2. The manganese-based sodium ion battery positive electrode material according to claim 1, characterized in that The Na x M1 a Fe b Mn c In O2, 0.7≤x≤0.9, 0.1≤a≤0.35, 0.1≤b≤0.
3.
3. The manganese-based sodium ion battery positive electrode material according to claim 1, characterized in that The Na x M1 a Fe b Mn c The peak intensity ratio of O2 is 0.6≤I (003) / I (104) ≤0.
9.
4. The manganese-based sodium ion battery positive electrode material according to claim 1, characterized in that: 0.4≤I S / I B ≤0.7。 5. A method for preparing the manganese-based sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: A certain proportion of Na salt, M1 source, Fe source and Mn source are fully mixed by ball milling method, and dried to obtain a reaction mixture precursor, wherein the M1 source, Fe source and Mn source are selected from oxides, acetates or nitrates of corresponding metals; S2: calcining the reaction mixture precursor of step S1 at 700° C.-800° C. for 2-6 hours to obtain a calcined precursor 1; S3: calcining the calcined precursor 1 in step S2 at 800° C.-1050° C. for 10-20 h to obtain a calcined precursor 2; S4: rapidly cooling the calcined precursor 2 to 400-600° C. and maintaining the temperature for 3-6 hours to obtain a positive electrode material precursor; S5: Naturally cool the positive electrode material precursor to room temperature to obtain a manganese-based sodium ion battery positive electrode material.
6. The preparation method according to claim 5, characterized in that: The calcination temperature of step S2 is 750°C-800°C, and the heating rate is 2-10°C / min.
7. The preparation method according to claim 5, characterized in that: The calcination temperature of step S3 is 900°C-1000°C, and the heating rate is 2-5°C / min.
8. The preparation method according to claim 5, characterized in that: In step S4, the calcined precursor 2 is rapidly cooled to 430-560°C and maintained for 4-5 hours.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the manganese-based sodium ion battery positive electrode material according to any one of claims 1 to 4.
10. A sodium ion secondary battery, characterized in that: The sodium ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet is the positive electrode sheet according to claim 9.
